2021
DOI: 10.32598/ijmtfm.v11i3.33949
|View full text |Cite
|
Sign up to set email alerts
|

Visual Disturbances in Patients With Acute Methanol Poisoning: A Cross-sectional Study

Abstract: Background: Methanol poisoning is a serious problem in public health, especially in developing countries. The present study aimed to evaluate the incidence of visual disturbances in patients with acute methanol poisoning in the south of Iran. Methods: This cross-sectional study (from 21/March/2014 to 21/March/2019) was conducted on all adult patients’ medical records who were referred to Ali-Asghar Hospital in Shiraz City, Iran, with acute methanol poisoning. The required data were collected using a data-gathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Also, lack of public awareness about the prevention and treatment of COVID-19, different types of alcohol, hazards of toxic alcohol, and how to use it properly as well as fear and concern from being infected by the virus led to wide use of alcohol-based detergents, especially methanol [ 22 , 32 , [36] , [37] , [38] ]. Methanol has few disinfectant properties, and oral methanol consumption is associated with severe intoxication, blindness, and death [ 17 ]. Many people thought drinking or gargling alcohol-based drinks may protect and disinfect their bodies against COVID-19, when some evidence suggested that people infected with COVID-19 have the virus on their stool and gastrointestinal system [ 5 , 8 , 22 , 30 , 32 , 41 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, lack of public awareness about the prevention and treatment of COVID-19, different types of alcohol, hazards of toxic alcohol, and how to use it properly as well as fear and concern from being infected by the virus led to wide use of alcohol-based detergents, especially methanol [ 22 , 32 , [36] , [37] , [38] ]. Methanol has few disinfectant properties, and oral methanol consumption is associated with severe intoxication, blindness, and death [ 17 ]. Many people thought drinking or gargling alcohol-based drinks may protect and disinfect their bodies against COVID-19, when some evidence suggested that people infected with COVID-19 have the virus on their stool and gastrointestinal system [ 5 , 8 , 22 , 30 , 32 , 41 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although products containing methanol are easily available, but illicit and informal productions are responsible for most methanol poisoning [ 13 ]. Methanol is highly toxic with high mortality and morbidity (including vision problems, especially blindness, metabolic, cardiac, and extensive neurological disorders) even after hospital discharge [ [14] , [15] , [16] , [17] ]. Hemorrhagic and non-hemorrhagic necrotic of basal ganglia, white matter necrosis and diffuse cerebral edema may lead to a serious prognosis [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of four studies included in this review indicated that the most commonly reported clinical manifestations of methanol poisoning were vision impairment and blindness, with severity depending on the dose. A study conducted by Mousavi Roknabadi et al, prior to the COVID-19 pandemic in Shiraz, Iran, reported that 75% of individuals with acute methanol poisoning experienced visual disturbances (30). Similarly, a study in Saudi Arabia in 2015 by Galvez-Ruiz et al noted that methanol poisoning could cause vision loss within 12 to 48 hours due to severe, painless, bilateral damage to the optic nerve (31).…”
Section: Discussionmentioning
confidence: 98%